LAJU TIMBULAN, DENSITAS SAMPAH LEPAS SERTA KOMPOSISI SAMPAH DI KECAMATAN BARABAI KABUPATEN HULU SUNGAI TENGAH - Muhammad Sadiqul Iman; Anissa Fitri; Arya Wicaksana; Nova Annisa (EnviroScienteae, 2023)
The rate of waste generation increases along with the pace of urbanization which is accompanied by the acceleration of economic development and rapid technological developments in society. The study location is Barabai Sub-district, one of the sub-districts and the capital of Hulu Sungai Tengah District (HST). The sampling method used the SNI 19-3964-1994 method regarding the method of taking and measuring samples of the generation and composition of urban waste and the approach using Weigh Volume Analysis (WVA). Sampling was carried out on a Dump Truck with a police number DA 926 E, because it can represent the rate of generation of residential waste which is domestic waste. Office waste, school waste and other public facilities that represent the rate of non-domestic waste generation. The conclusion is that the rate of waste generation in Barabai Sub-district is 0,176 kg/person/day. The uncompacted waste density in Barabai Sub-district is 220,95 kg/m3. The composition of the most waste is food waste + yard waste, with a percentage reaching 42,96%. Plastic waste and diapers & sanitary napkins are the most common types of waste after food waste + yard waste, with a percentage of 20% and 17.73%.